PENINGKATAN PENGETAHUAN DAN SIKAP TENTANG PENCEGAHAN MIOPIA MELALUI MEDIA EDUKASI PERMAINAN KOTAK POS PADA SISWA SDN 22 ANDALAS BARAT KOTA PADANG - Arifanni Ulmy; John Amos; Neni Fitra Hayati; Novelasari Novelasari; Sorpiyani Munthe (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2026)
Background: Myopia is a common visual disorder among school-aged children, often caused by habits such as reading at a very close distance and excessive use of digital devices. The Padang City Health Office reported 3,909 cases of myopia in 2023, while school health screening at SDN 22 Andalas Barat conducted by the Andalas Community Health Center identified 67 students with visual impairment. Early prevention efforts are needed through educational methods that are engaging and suited to children’s characteristics. Objective: This study aimed to determine the improvement in students’ knowledge and attitudes regarding myopia prevention through the “Kotak Pos” educational game at SDN 22 Andalas Barat, Padang City. Methods: This study employed a mixed methods approach combining qualitative and quantitative methods. Qualitative data were collected through in-depth interviews with triangulation of sources, while quantitative data used a quasi-experimental one-group pretest-posttest design with a total of 66 students as the sample. Informants included students, school health teachers, eye health staff, language experts, and graphic design specialists. Quantitative data were analyzed using the Wilcoxon test. Results: The median knowledge score increased from 6 to 13, while the median attitude score improved from 44.5 to 58. The Wilcoxon test showed significant differences before and after the intervention (p<0.05). Conclusion: The Kotak Pos educational game effectively improved students’ knowledge and attitudes regarding myopia prevention, suggesting its potential as an alternative strategy for eye health education in elementary schools.